Effects of Incorporation of Moringa Oleifera Leaf Meal on Production Performance of Rhode Island Red Laying Hens - , D.G. Vaghamashi; D. D. Garg; G. P. Sabapara; H. H. Savasani; M. R. Chavda; K. B. Vala; J. A. Chavda; A. A. Mathakiya; B. J. Solanki (Indian Journal of Animal Nutrition, 2024)
The objective of the study was to evaluate the effect of Moringa oleifera leaf meal (MOLM) on production performance of Rhode Island Red (RIR) layers. One hundred and eighty, 24-week-old Rhode Island Red layer birds were randomly allotted to four dietary treatments having replicates with 15 birds in each. The treatments were T1 (Control: Basal diet); T2: 1% MOLM in basal diet; T3: 3% MOLM in basal diet; T4: 5% MOLM in basal diet. The results revealed that average daily feed intake per bird (g/day) was higher (P0.05). No statistical difference for feed conversion ratio (FCR) was observed between groups or within group. The average monthly HDEP % of experiment was significantly (PT3>T2>T1 with significant difference between T1 and T4. In the current study, total feed intake per bird was not differed by MOLM addition, but total feed cost per bird was significantly decreased in MOLM fed groups. Additionally, more number of eggs laid by MOLM fed groups leads to higher receipt from egg sale and net return over feed cost.